2019
DOI: 10.1021/acs.est.8b04200
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Stimulates Cadmium Detoxification in Caenorhabditis elegans through Thiols-Mediated Nanoparticles Formation and Secretion

Abstract: Antagonism between heavy metal and selenium (Se) could significantly affect their biotoxicity, but little is known about the mechanisms underlying such microbial-mediated antagonistic processes as well as the formed products. In this work, we examined the cadmium (Cd)–Se interactions and their fates in Caenorhabditis elegans through in vivo and in vitro analysis and elucidated the machinery of Se-stimulated Cd detoxification. Although the Se introduction induced up to 3-fold higher bioaccumulation of Cd in C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…Our previous work showed that Se can induce serial biotransformation of Cd in C. elegans distinct from that under Cd-alone condition, which ultimately leads to the formation of CdSe NPs. 17 Here, in situ Se K-edge (12658 eV) XANES spectrometry was performed on C. elegans to further unveil the compositional and structural changes of the Se and Cd species in vivo. The normalized XANES spectrum showed a distinct peak similar to that of CdSe (12659.5 eV) (Figure 1), indicating that the ingested Se IV (i.e., selenite) has been fully transformed into organoselenium and Se -II (i.e., CdSe).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous work showed that Se can induce serial biotransformation of Cd in C. elegans distinct from that under Cd-alone condition, which ultimately leads to the formation of CdSe NPs. 17 Here, in situ Se K-edge (12658 eV) XANES spectrometry was performed on C. elegans to further unveil the compositional and structural changes of the Se and Cd species in vivo. The normalized XANES spectrum showed a distinct peak similar to that of CdSe (12659.5 eV) (Figure 1), indicating that the ingested Se IV (i.e., selenite) has been fully transformed into organoselenium and Se -II (i.e., CdSe).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our previous study has demonstrated an obvious correlation between the genetic expression of these peptides and the Se and Cd exposure. 17 However, direct evidence regarding their specific roles and contributions to the NPs formation is still lacking. To clarify this issue, here we selectively silence specific genes using RNAi techniques.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations